(untitled) (DAPesquisa, 2020)
Woven into epistolary lines, this text establishes a reflection on academic writing in a performative perspective, revealing the experience as the main dynamo of texts germinated in investigations in the performing arts in Brazil. From the friction between body and writing, powerful moments are generated, raising the performance layers of this preliminary, f(r)ictional act. Using as a metaphor a letter addressed to the feminist writer Virgínia Woolf and in a pretension to take her essay A room of one´s own ([1929] 2014), as a playful inspiration, we are considering an arts academy steeped in performance and poetry.